Cell-mediated immune responses to influenza vaccination in Wegener's granulomatosis. Issue 5 (12th July 2009) - Holvast, Albert; de Haan, Aalzen; van Assen, Sander; Stegeman, Coen A; Huitema, Minke G; Huckriede, Anke; Benne, Cornelis A; Westra, Johanna; Palache, Abraham; Wilschut, Jan; Kallenberg, Cees G M; Bijl, Marc
Abstract : Background: Both antibody and cell-mediated immune responses are involved in the defence against influenza. In Wegener's granulomatosis (WG), antibody responses to influenza vaccination appear to be similar to those in healthy controls, but cell-mediated responses have not been studied. Objective: To determine whether cell-mediated responses to influenza vaccination in WG vary from those in controls. Methods: Twenty-five patients with WG and healthy controls received subunit influenza vaccine. Peripheral blood mononuclear cells were obtained before and 1 month after vaccination. Cell-mediated responses to A/H1N1 and A/H3N2 were assessed using interferon γ (IFNγ) ELISpot and intracellular cytokine staining for IFNγ, tumour necrosis factor and interleukin 2. Results: Before vaccination, patients and controls showed similar recall responses to A/H1N1 and A/H3N2. After vaccination, patients and controls showed similar levels of increase in spot-forming cells against A/H1N1 and A/H3N2. By flow cytometry, upon vaccination, proportions of cytokine-producing CD4 T cells increased in patients and controls for A/H1N1 and A/H3N2. Conclusions: Cell-mediated responses to influenza vaccination in patients with WG are comparable to those in healthy controls. Dutch Trials Register number NTR1130.